Pengembangan Media Gapinsa Pembelajaran Matematika Materi Pengukuran Kelas V Sekolah Dasar - Ahmadah Yustica Putri; Arissona Dia Indah Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The research conducted aims to develop Gapinsa learning media for Mathematics subjects, measurement materials in class V. The developed media can be used to assist in learning activities so that it can be used to overcome problems that occur. The research was conducted at UPT SD Negeri 248 Gresik in the 2022/2023 school year. The type of research used is research and development or called R&D using the ADDIE model. The methods used in this study are observation and interviews used to find out information or the needs of students in the classroom, documents to strengthen evidence during research activities, validation to test the feasibility of the media and questionnaires to determine the response of learning media to the media developed. The subjects of the research conducted amounted to 36 students consisting of 20 male students and 16 female students in the 2022/2023 school year. Based on the results of research conducted by researchers through the development of Gapinsa learning programs, measurement materials have gone through validity tests, including the validation stage, media experts get a score of 85% in the